Pemanfaatan Sistem Akuntansi Keuangan Tingkat Instansi (Sakti) dalam Pengelolaan Keuangan di Ditjen Binwasnaker dan K3: Transformasi Akuntansi Digital - Rachmarini Dian Anggraini (Riviera Publishing, 2025)
Aplikasi Sistem Akuntansi Keuangan Tingkat Instansi (SAKTI) issued by Ministry of Finance of the Republic Indonesia is a digital accounting information technology development specifically for use in the public sector. The SAKTI application aims to improve efficiency and accuracy in state financial management. This study identifies the challenges and benefits of implementing SAKTI, as well as how this system can contribute to improving the quality of government financial reporting. This research uses a qualitative case study method with data collection techniques through interviews and direct observation.